2012
DOI: 10.1021/om300657z
|View full text |Cite
|
Sign up to set email alerts
|

Half-Sandwich Ruthenium-Phosphine Complexes with Pentadienyl and Oxo- and Azapentadienyl Ligands

Abstract: Treatment of RuCl2(PPh3)3 and RuHCl­(PPh3)3 with the tin compound CH2C­(Me)­CHC­(Me)­CH2SnMe3 gives the corresponding acyclic pentadienyl half-sandwich (η5-CH2C­(Me)­CHC­(Me)­CH2)­RuX­(PPh3)2 [X = Cl, (2); H, (3)]. The steric congestion in 2 is most effectively relieved by formation of the cyclometalated complex (η5-CH2C­(Me)­CHC­(Me)­CH2)­Ru(C6H4PPh2)­(PPh3) (4). Addition of 1 equiv of PHPh2 to (η5-CH2CHCHCHCH2)­RuCl­(PPh3)2 (1) affords the chiral complex (η5-CH2CHCHCHCH2)­RuCl­(PPh3)­(PHPh2) (5), while compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…Over the past decade various studies on the chemistry of the pentadienyl (Pdl = C 5 H 7 ) ligand have given valuable insight into the reactivity of the Pdl ligand in comparison to the similar, and more well known, cyclopentadienyl ligand (Cp). A wide variety of Pdl ligands have been synthesized, and studies have revealed several unique properties of Pdl, , leading to numerous possible applications of metal pentadienyl reaction chemistry. , Metal complexes containing the Pdl ligand often exhibit interesting reactivity due to the accessibility of a range of η 1 , η 3 , and η 5 bonding modes . While the Pdl ligand has an extreme tendency to bond to transition metals in low oxidation states as a result of the high δ acidities of these ligands, higher valent (≥+3) complexes have been reported. , Previous studies on Pdl ligands also show a marked reversal in the favorability of the bonding in comparison to that for the Cp ligand depending on the metal oxidation state, leading to differences in structure and reactivity of the low-valent and high-valent metal complexes. , The Pdl ligand bonds more strongly to a metal center than does a Cp ligand in lower valent metal complexes, and the reverse is observed for high-valent metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade various studies on the chemistry of the pentadienyl (Pdl = C 5 H 7 ) ligand have given valuable insight into the reactivity of the Pdl ligand in comparison to the similar, and more well known, cyclopentadienyl ligand (Cp). A wide variety of Pdl ligands have been synthesized, and studies have revealed several unique properties of Pdl, , leading to numerous possible applications of metal pentadienyl reaction chemistry. , Metal complexes containing the Pdl ligand often exhibit interesting reactivity due to the accessibility of a range of η 1 , η 3 , and η 5 bonding modes . While the Pdl ligand has an extreme tendency to bond to transition metals in low oxidation states as a result of the high δ acidities of these ligands, higher valent (≥+3) complexes have been reported. , Previous studies on Pdl ligands also show a marked reversal in the favorability of the bonding in comparison to that for the Cp ligand depending on the metal oxidation state, leading to differences in structure and reactivity of the low-valent and high-valent metal complexes. , The Pdl ligand bonds more strongly to a metal center than does a Cp ligand in lower valent metal complexes, and the reverse is observed for high-valent metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of compound 7 with 1 equivalent of triflic acid in diethyl ether leads to the formation of dark red 8 , the monoprotonation product. The NMR spectra of 8 indicate that it is a single isomer in which protonation has occurred at the iridium center and the azapentadienyl ligand has coordinated in an unusual η 3 , η 1 fashion involving both its allyl moiety and its nitrogen lone pair (see Scheme ) . In the 1 H NMR spectrum, the metal hydride signal is observed at δ −28.79 and is a doublet of doublets due to coupling to two inequivalent PEt 3 ’s.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that 4a and 4b represent, to the best of our knowledge, the first structurally characterised half-sandwich pentadienyl ruthenium complexes with a (formal) electron count of 16, and previously described pentadienyl species are usually 18-electron complexes with common three-legged piano-stool ( pseudo-tetrahedral) geometries. 16,19,27,28 29,30 In contrast, a significantly larger number of 16-electron complexes are known that contain the sterically more demanding (η 5 -C 5 Me 5 )Ru fragment. [31][32][33] Fig.…”
Section: Preparation and Electronic Structure Of The Half-open Ruthen...mentioning
confidence: 99%